PENINGKATAN KEMAMPUAN BERPIKIR MATEMATIS SISWA PADA MATERI BANGUN DATAR MELALUI MODEL PEMBELAJARAN PROYEK TERINTEGRASI STEM - Warih, Kanti warih ade (Media Pendidikan Matematika, 2020)
Students obstacle in the concept of shapes (triangles) based for researchers to implement meaningful teaching and learning methods using project learning models integrated with STEM approachment. In STEM-learning projects, students are trained to solve mathematical problems through projects that are integrated with one or another field. This classroom research conducted in 2 cycles with 4 stages each cycle, were plan, action, observ, and reflect. The purpose of this study was to determine the students' mathematical thinking abilities increasing. Subjects were students of class VIII of SMPN 4 Taliwang. The instruments used observation sheets and tests. The data obtained were analyzed and concluded as descriptive. The results of the learning implementation  showed an increase from good to very good. Whereas the students mathematical thinking ability from pre-test and post-test result in 1st cycle has increased from 25 average score to 72. And in 2nd cycle achieved average scores 80 on post-test from 35 pre-test score.  Seen from passing grade minimum, found that 1 person who passed on 1st cycle pre test to 16 persons passed on post test. And at the 2nd cycle, students who passed the pre-test 3 persons became 19 persons on post-test. At the finally tasks, each student group produced a one leg tabel models based on midpoint of combined triangles concepts.  Based on these data, this study was declared successful according to the increasing achievement. Researcher's suggestion is using STEM project learning recommended for creating joyful and meaningful learning mathematics.